Modifications of protein-related compounds of beef minced meat treated by high pressure. (August 2018) - Guyon, Claire; Le Vessel, Valentin; Meynier, Anne; de Lamballerie, Marie
Abstract: In this study, we evaluated the modifications of the protein-related compounds of minced beef treated with high pressure, including refrigeration after treatment. The free amino acid content, protein carbonyls and free thiol groups were assessed. High pressure up to 200 MPa had a significant effect. Above 300 MPa, irreversible structural changes occurred, with an increase in the protein oxidation products and a modification of the amounts of amino acids after 14 days of storage. Protein carbonyls and the free thiols were correlated with the free amino acids. These results showed that protein modifications under pressure result from both conformational and chemical changes, possibly associated with lipid changes under high-pressure treatment. Highlights: High Pressure treatment has a great potential in meat preservation. Above 300 MPa, high Pressure treatment increases the protein oxidation in beef minced meat. High Pressure treatment modifies the amount of free amino acids after 14 days of storage. Protein carbonyls, free thiols and free amino acids evolution are correlated.